Dampak Media Sosial Terhadap Krisis Moral - Febriyan Ichlasul Imam; Wahyono; Muhammad Syaiful Rahmat Ariyadi; Wawan Supriyono (Halaqatuna, 2026)
This study examines the impact of social media on moral crisis from an Islamic public ethics perspective, focusing on how the development of digital space influences residents’ behaviour and the quality of public ethics. The rapid growth of social media has created a new, freer, and instant communication pattern. On the other hand, it has also triggered various moral crises, such as hoaxes, hate speech, harassment, and the loss of mutual respect. From an Islamic perspective on public ethics, these problems arise when basic values such as honesty, responsibility, politeness, and the obligation to protect the public interest are not applied in online interactions. This study emphasizes that the moral crisis in social media is not only a matter of user behaviour, but also reflects weak self-monitoring and a diminished spiritual awareness in utilizing technology. Therefore, strengthening digital literacy based on Islamic values, implementing the principles of amar ma’ruf nahi munkar in the virtual realm, and establishing a culture of polite communication are strategic steps to reorganize public morality in the digital world. Thus Islamic public ethics can play a significant role in building a digital space that is more dignified, safe, and oriented towards social welfare.